2014
DOI: 10.11606/issn.2176-7793.v45i1p1-33
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic Review of the species complex of Crossodactylus dispar A. Lutz, 1925 (Anura, Hylodidae)

Abstract: Taxonomic Review of The species complex of CrossodaCtylus dispar a. luTz, 1925 (anuRa, hylodidae) BRuno v.s. pimenTa 1 caRlos alBeRTo Gonçalves cRuz 2 ulisses caRamaschi 2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 20 publications
0
16
0
3
Order By: Relevance
“…THE FAMILY Hylodidae includes the genera Crossodactylus Dú meril and Bibron, 1841 (14 species), Hylodes Fitzinger, 1826 (24 species), and Megaelosia Miranda- Ribeiro, 1923 (7 species;Frost 2014;Pimenta et al 2014). Crossodactylus is composed of stream-dwelling diurnal frogs that are distributed from the state of Alagoas in northeastern Brazil, south to the state of Rio Grande do Sul in southern Brazil, and further into southern Paraguay and northern Argentina Caramaschi 1993 ''1992'';Frost 2014).…”
mentioning
confidence: 99%
“…THE FAMILY Hylodidae includes the genera Crossodactylus Dú meril and Bibron, 1841 (14 species), Hylodes Fitzinger, 1826 (24 species), and Megaelosia Miranda- Ribeiro, 1923 (7 species;Frost 2014;Pimenta et al 2014). Crossodactylus is composed of stream-dwelling diurnal frogs that are distributed from the state of Alagoas in northeastern Brazil, south to the state of Rio Grande do Sul in southern Brazil, and further into southern Paraguay and northern Argentina Caramaschi 1993 ''1992'';Frost 2014).…”
mentioning
confidence: 99%
“…Vocal sacs have been reported as absent in C. aeneus and C. trachystomus (Müller, ) and single, subgular in C. aeneus, C. bokermanni, C. cyclospinus, C. dantei, C. gaudichaudii, C. lutzorum, C. schmidti , and C. trachystomus (Lynch, ; Pimenta, Cruz, & Caramaschi, ; Pimenta et al, ). Subtle bilobular expansions have been reported only in C. boulengeri (Pimenta, Wachlevski, & Cruz, ), C. caramaschii (Bastos & Pombal, ), and C. dispar (Pimenta et al, ). Nevertheless, study of internal vocal sac anatomy revealed the presence of paired, lateral vocal sacs in C. aeneus , C. boulengeri , C. cyclospinus , C. dantei , C. dispar , C. gaudichaudii , C. grandis , and C. schmidti .…”
Section: Discussionmentioning
confidence: 99%
“…This is probably why most species of Crossodactylus have been reported to have single, subgular sacs in the taxonomic literature. Vocal sacs have been reported as absent in C. aeneus and C. trachystomus (M€ uller, 1924) and single, subgular in C. aeneus, C. bokermanni, C. cyclospinus, C. dantei, C. gaudichaudii, C. lutzorum, C. schmidti, and C. trachystomus (Lynch, 1971;Pimenta, Cruz, & Caramaschi, 2014;Pimenta et al, 2015). Subtle bilobular expansions have been reported only in C. boulengeri (Pimenta, Wachlevski, & Cruz, 2008), C. caramaschii (Bastos & Pombal, 1995), and C. dispar (Pimenta et al, 2014).…”
Section: Position Of the Vocal Sacsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since then, there has been an increase in species inventories performed throughout the state, improving the knowledge about the composition and distribution of the state's amphibian fauna (e.g., Almeida-Gomes et al, 2008, 2014Carvalho-e-Silva et al, 2008;Siqueira et al, 2011a, b;Salles et al, 2009;Silva-Soares et al, 2010;Vrcibradic et al, 2011;Martins et al, 2012Martins et al, , 2014Telles et al, 2012;Bittencourt-Silva & Silva, 2013;Pontes et al, 2015). Additionally, several species have been added to the state's amphibian list, either through reports of new occurrence records (e.g., Vrcibradic et al, 2006;Silva-Soares et al, 2009;Silveira et al, 2010;Caram et al, 2011;Pederassi et al, 2015), or through descriptions, revalidations or reassessments of taxa (e.g., Carvalho-e-Silva & Carvalho-e-Silva, 2005;Caramaschi & Pombal, 2006;Canedo & Pombal, 2007;Pombal et al, 2008;Prado & Pombal, 2008;Silva & Alves-Silva, 2008;Carvalho-e-Silva et al, 2009Targino et al, 2009;Pombal, 2010;Pombal & Izecksohn, 2011;Weber et al, 2011;Silva & Alves-Silva, 2011;Nunes et al, 2012;Silva & Ouvernay, 2012;Dias et al, 2013;Caramaschi et al, 2013;Pimenta et al, 2014;Hepp et al, 2015).…”
Section: Introductionmentioning
confidence: 99%